Developing Story Book Media to Improve Emotional Management Skills in 5-6 Year Old Children - Husnul Khotimah; Azi Matur Rahmi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This research aims to develop a mediastory book to develop the emotional management skills of 5–6-year-old children in Cibitung District. The research was motivated by children's low ability to recognize and control emotions and the limited availability of social-emotional learning media in early childhood education (PAUD). The research method used was Research and Development(R&D) with the ADDIE model, which covers the stages analysis, design, development, implementation, and evaluation. The research subjects consisted of children aged 5–6 years and kindergarten teachers in Cibitung District. The results of the study showed that the mediastory book has a very high level of validity, with a material validation score of 98.5% and a media validation score of 85.3%. The media also achieved a practicality score of 90% and effectively increased children's emotional management skills from 71% to 93%. Thus, the Mediastory book is suitable for use as a social-emotional learning medium for early childhood.